Meningkatkan Kemampuan Berpikir Simbolik Anak Melalui Media Toples Simbol Pada Anak Usia Dini 4-5 Tahun Di RA Al Kubro Kecamatan Tarogong Kaler Kabupaten Garut - Ulfah, Fitria; Wandani, Sani (LP2M STAI Al-Musaddadiyah Garut, 2024)
This research was motivated by the low symbolic thinking abilities of children in group A at RA Al Kubro, such as children not being able to recognize and name symbols, numbers and letters. This research aims to improve children's ability to think symbolically by using symbol jar media. The method used is the classroom action research (CAR) method using the Kemmis and Mc Taggart model. Data collection uses observation and documentation techniques. The subjects in this research were all students from group A. This research was carried out in three cycles, each cycle consisting of two meetings. The results of the research showed that the percentage of children's symbolic thinking abilities before the cycle was 10%, then there was an increase in the first cycle to 35%. Meanwhile, the increase in cycle II was 70% and cycle III was 85%. Thus, the ability to think symbolically in early childhood in the A RA Al Kubro group before being given action using the symbol jar media experienced a significant increase. Keywords: symbolic thinking, learning media symbol jar, early childhood